ROLE OF HEART RATE REDUCTION WITH IVABRADINE IN LEFT VENTRICULAR FAILURE: IVABRADINE AND HEART RATE REDUCTION IN LEFT VENTRICULAR FAILURE - Batool, Safia; Waris, Jamal; Sajid, Muhammad Usman; Nisar, Shazia; Khan, Imran; Mushtaq, Hina (Pakistan Armed Forces Medical Journal, 2020)
Objective: To compare mean heart rate reduction in Ivabradine and placebo group in left ventricular failurepatients.Study Design: Quasi experimental study.Place and Duration of Study: Study was conducted at CMH, Kharian, from Jul 2018 to Dec 2018.Methodology: 64 patients participated in the study. They were randomly divided into two groups of 32each. One group was given Tab Ivabradine (10 mg twice a day) while second group received a placebo for aperiod of 4 weeks. After 4 weeks each patient was evaluated and heart rate, systolic and diastolic blood pressure were recorded. Mann-whitney U test selected to compare heart rate and ages of both groups t- test used to compare systolic and diastolic blood pressure among both groups. Chi-square test used to determine the association of heart rate between two groups. A p-value ≤0.05 was considered significant.Results: Median (IQR) heart rate was significantly lower in Ivabradine group 58.3 (4) as compared to placebo64.1(1) (p